HADIS DALAM PUSARAN PEMILU (Mengkaji Pemahaman Hadis MUI dalam Fatwa Haram Golput Pemilu) - Hariono, Duwi (IAIN Kediri, 2018)
Integrating hadith from the past with the contemporary social problem is not always easy. It is because hadith is a fixed text so that it cannot always be suitable with every problem developed outside its time. In a case of religious decision (fatwa) in which hadith is used, MUI has own way to connect between hadith and recent problems so that hadith can give answer on that problems. The haram decision on un-use choosing right in election is the example. In arranging that decision, hadith is placed together with other basis: al- Qur’an, fiqh, and ushul fiqh, then they are mixed together using qiyas as methodology basis of its interpretation. The result is subjective. However, there is no other way, and what has been done by MUI to use hadith in religious decision (fatwa) has been correct. Keywords: hadith, MUI, understanding, un-use choosing right